Location of neonatal microglia drives small extracellular vesicles content and biological functions in vitro. Issue 1 (1st January 2020) - Murgoci, Adriana-Natalia; Duhamel, Marie; Raffo-Romero, Antonella; Mallah, Khalil; Aboulouard, Soulaimane; Lefebvre, Christophe; Kobeissy, Firas; Fournier, Isabelle; Zilkova, Monika; Maderova, Denisa; Cizek, Milan; Cizkova, Dasa; et al.
ABSTRACT: Combining proteomics and systems biology approaches, we demonstrate that neonatal microglial cells derived from two different CNS locations, cortex and spinal cord, and cultured in vitro displayed different phenotypes upon different physiological or pathological conditions. These cells also exhibited greater variability in terms of cellular and small extracellular vesicles (sEVs) protein content and levels. Bioinformatic data analysis showed that cortical microglia exerted anti-inflammatory and neurogenesis/tumorigenesis properties, while the spinal cord microglia were more inflammatory. Interestingly, while both sEVs microglia sources enhanced growth of DRGs processes, only the spinal cord-derived sEVs microglia under LPS stimulation significantly attenuated glioma proliferation. These results were confirmed using the neurite outgrowth assay on DRGs cells and glioma proliferation analysis in 3D spheroid cultures. Results from these in vitro assays suggest that the microglia localized at different CNS regions can ensure different biological functions. Together, this study indicates that neonatal microglia locations regulate their physiological and pathological functional fates and could affect the high prevalence of brain vs spinal cord gliomas in adults.